THE EFFECT OF APPLYING SAVI MODEL ON STUDENTS’ SPEAKING ACHIEVEMENT IN ORAL DESCRIPTIVE TEXT - Azrina Manja; Anni Holila Pulungan (Universitas Negeri Medan, 2015)
This study was conducted as an attempt to find out the effect of applying SAVI model on Students’ students’ speakingAchievement in oral descriptive text. This study used the experimental design. The population of this study was the students of MAN Kualuh Hulu. The subject of this study was the 2013/2014 tenth grade students of MAN Kualuh Hulu. This study was conducted with two randomized groups namely experimental group and control group. The control group was taught by conventional method while experimental group was taught by applying SAVI model. The instrument used in this study was an objective test. To obtain the reliability of the test, the researcher used Kuder-Richardson (KR-21) formula. The calculation shows that the reliability was 0.67 (reliabity). The data were analyzed by using t-test. The calculation shows that t-observed (5.36) is higher than t-table (1.996) at the level of significance (α) 0.05 with the degree of freedom (df) 68. Therefore, null hypothesis (Ho) is rejected and alternative hypothesis (Ha) is accepted. It means that SAVI Model significantly affect the students’ speaking achievement in oral descriptive text.